I can do it! : [featuring Jim Henson's Sesame Street Muppets] - Albee, Sarah; Di Fiori, Lawrence (New York : Random House, Children's Television Workshop, 1997)
Zoe and her friends at Sesame Street can do all sorts of things, especially when they help each other.
"CTW Sesame Street"--Page 4 of cover.
Keywords: Helpfulness -- Juvenile fiction; Puppets -- Juvenile fiction; Stories in rhyme -- Juvenile fiction; Helpfulness -- Fiction; Puppets -- Fiction; Stories in rhyme